2019
DOI: 10.3389/fnhum.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

Production Variability and Categorical Perception of Vowels Are Strongly Linked

Abstract: Theoretical models of speech production suggest that the speech motor system (SMS) uses auditory goals to determine errors in its auditory output during vowel production. This type of error calculation indicates that within-speaker production variability of a given vowel is related to the size of the vowel’s auditory goal. However, emerging evidence suggests that the SMS may also take into account perceptual knowledge of vowel categories (in addition to auditory goals) to estimate errors in auditory feedback. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Thus the magnitude of adaptation (learning from errors) and error sensitivity are larger when errors are task relevant. Based on the results of this study and previous studies (Chao et al 2019;Guenther 2016;Niziolek and Guenther 2013;Perkell 2012;Villacorta et al 2007), we speculate that the CNS uses a combination of strategies to determine relevance of errors and to assign weights to perceived auditory errors. First, the CNS may use the distance between the received auditory feedback and predicted auditory consequences of its speech motor outputs (auditory prediction error).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus the magnitude of adaptation (learning from errors) and error sensitivity are larger when errors are task relevant. Based on the results of this study and previous studies (Chao et al 2019;Guenther 2016;Niziolek and Guenther 2013;Perkell 2012;Villacorta et al 2007), we speculate that the CNS uses a combination of strategies to determine relevance of errors and to assign weights to perceived auditory errors. First, the CNS may use the distance between the received auditory feedback and predicted auditory consequences of its speech motor outputs (auditory prediction error).…”
Section: Discussionsupporting
confidence: 62%
“…These two vowels were selected because the vowel // was perturbed toward the vowel /ae/ in the adaptation task, and therefore, it was important to examine participants' perception of the auditory perturbations. We used a procedure similar to the one used in our previous study (Chao et al 2019). Based on the extracted median tokens, a participant-specific vowel continuum (-ae) was generated in 10 successive equal increments (in Hz) such that the first token coincided with the participant's median // and the last token coincided with the participant's median /ae/ (Fig.…”
Section: B E Dmentioning
confidence: 99%
“…However, this potentially introduces a mismatch between the perceptual measure and the production variability measure, since participants are likely to make different perceptual judgments when hearing their own recorded speech versus model speakers' speech. This point is bolstered by the findings reported in Chao et al (2019), where there was a strong correlation between participants' categorical perception boundary and a productionbased categorical boundary for the same /ε/ -/ae/ contrast. In that study, participants' own speech was used to create the synthesized vowel continuum for the identification task, specifically using participants' median F1 and F2 values for each vowel as the two endpoints.…”
Section: Relationship Between Perception Ability Production Contrast Distinctness and Production Variabilitymentioning
confidence: 55%
“…However, averaging over repeated trials omits information about trial-to-trial variability, which may be of relevance to both perception and production. In fact, Chao et al (2019) found that the location of participants' perceptual boundary between /ε/-/ae/ in American English, derived using an identification task, was correlated with the location of the boundary between these categories in production space, derived based on the distribution of tokens across repeated productions. That is, the categorical boundary was further away from the more variable vowel in the contrast.…”
Section: Links Between Speech Perception and Production Variabilitymentioning
confidence: 99%
See 1 more Smart Citation